THE EFFECT OF ISLAMIC CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, FINANCING DECISIONS, AND COMPANY SIZE ON SHARIA BANKING FINANCIAL PERFORMANCE 2014-2018 - Trispada Sinta; Indra Chaniago; Jaka Darmawan; Yan Aditiya Pratama (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to determine the effect of Islamic corporate governance, intellectual capital, funding decisions, and company size on the financial performance of Islamic banking companies in 2014-2018. The type of study used the associative method with hypothesis testing using Multiple Linear Regression. The results of this study indicated that the Islamic corporate governance variable is measured using (Bahasa: Jumlah Rapat Dewan Komisaris (JRDK)), Islamic corporate governance as measured by (Bahasa: Ukuran Dewan Direksi (UUD)), funding decisions and company size had a significant effect on the financial performance of sharia banking companies in 2014-2018. Meanwhile, the Islamic corporate governance variable measured using (Bahasa: Jumlah Rapat Dewan Pengawas Syariah (JRDPS)), Islamic corporate governance measured using (Bahasa: Ukuran Komite Audit (UKA)), Islamic corporate governance measured using (Bahasa: Ukuran Audit Eksternal (AE)) and intellectual capital variables did not have a significant effect on the financial performance of Islamic banking companies in 2014-2018.Keywords: Islamic Corporate Governance, Intellectual Capital, Funding, Size, Financial Performance